Foreign trade barriers in South Korea affecting the food and pharmaceutical industries. - Cheng, Koh Yeu. (2008)
This paper starts with a review of foreign trade barriers in South Korea, as reported by various published sources, with a detailed look at the food and pharmaceutical industries.